2005
DOI: 10.1111/j.1365-2621.2005.tb09044.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fungal Growth on Wheat and Rye Bread by Modified Atmosphere Packaging and Active Packaging Using Volatile Mustard Essential Oil

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: : : : : Wheat and r Wheat and r Wheat and r Wheat and r Wheat and ry y y y ye br e br e br e br e bread ar ead ar ead ar ead ar ead artificially inoculated with molds w tificially inoculated with molds w tificially inoculated with molds w tificially inoculated with molds w tificially inoculated with molds wer er er er ere packed in modified atmospher e packed in modified atmospher e packed in modified atmospher e packed in modified atmospher e packed in modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…When incorporated into the atmosphere around bread, mustard oil and its primary antimicrobial component, allyl isothiocyanate, have been shown to effectively inhibit the growth of several bread-spoilage fungi, including Aspergillus flavus, Endomyces fibuliger, Penicillium spp. and Pichia anomala [188,189]. Mould and yeast counts on sweet cherries were significantly reduced in modified atmospheres containing eugenol, thymol or menthol but not eucalyptol [190].…”
Section: Antifungal Activitymentioning
confidence: 85%
“…When incorporated into the atmosphere around bread, mustard oil and its primary antimicrobial component, allyl isothiocyanate, have been shown to effectively inhibit the growth of several bread-spoilage fungi, including Aspergillus flavus, Endomyces fibuliger, Penicillium spp. and Pichia anomala [188,189]. Mould and yeast counts on sweet cherries were significantly reduced in modified atmospheres containing eugenol, thymol or menthol but not eucalyptol [190].…”
Section: Antifungal Activitymentioning
confidence: 85%
“…Moulds were not detected until the final testing period (data not shown), with levels of 3.7, 4.9 and 1.6 log 10 CFU g −1 on the uninoculated control, inoculated control and 200 µg kg AIT treatment, respectively. The inhibitory nature of low AIT concentrations toward yeast 30 and mould 31 was both expected and desired.…”
Section: Westphalian Ham Microbiological Changesmentioning
confidence: 97%
“…The oxygen level inside the package limits the shelf life of the product in terms of aerobic microorganisms (Ponte et al 1993). Although there have been number of researches related with the MAP technique on different foods, limited research have been reported on the MAP technique to prolong shelf-life of bread (Nielsen and Rios 2000;Suhr and Nielsen 2005;Fernandez et al 2006). Shelf-life for many bakery foods can be extended by modifying the gas concentration inside the package.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its insolubility in water, the presence of nitrogen in MAP food can prevent pack collapse that occurs when high concentrations of CO 2 are used ( Ponte et al 1993;Smith and Simpson 1995;Kotsianis et al 2002). The general recommendation for MAP of bakery products has been a mixture of 60% CO 2 :40% N 2 , but specific gas mixtures should be used for each type of product and mixtures have variations from 0 to 100% CO 2 balanced with N 2 (Farber 1991;Suhr and Nielsen 2005).…”
Section: Introductionmentioning
confidence: 99%